Migração ambiental: expropriação territorial pela construção da Usina Hidrelétrica de energia Baixo Iguaçu - Paraná - Heinzmann , Clara Ermelinda (2022)
In Brazil, the agrarian profile is strongly accompanied by an industrial and urban reality, marked, however, by problems, including territorial expropriation, whose solutions constitute a great political-administrative and academic-social challenge. The issue becomes latent when territorial expropriation is a consequence of development projects already built or under construction that, through human interference, cause environmental, economic and social changes, and force individuals to move, as happens in construction. of hydroelectric power plants, thus causing environmental migration/displacement. Thus, the present work analyzes the deterritorialization process of expropriated families in the municipalities of Capanema and Capitão Leônidas Marques, in the State of Paraná, and describes the main economic and social impacts caused by the construction of the Baixo Iguaçu Hydroelectric Power Plant. In order to carry out the study, the deductive method and research of an exploratory, reflective and empirical nature were used. The research was based on primary and secondary data. The collection of primary data was carried out through technical procedures of field research, being used as a research instrument the structured, unidentified interview, through the technique of random sampling. Secondary data were collected from governmental and non-governmental entities, especially the IBGE. It was observed that the process of deterritorialization caused by the construction of the Baixo Iguaçu Hydroelectric Power Plant was a unilateral act and that most of the expropriated families received compensation that was not consistent with the real value of the land, and more, those who were not willing to negotiate on the terms proposed by the consortium, are still fighting in court to receive compensation. Regarding the economic impacts, at first, during the construction of the plant, there was an injection of resources, mainly in commerce, but on the other hand there was the loss of productive areas, causing damage to the local economy and also to the expropriated families. With regard to social impacts, which are often mitigated by compensatory measures, called social actions, proposed as a way to minimize or neutralize the damage caused by the construction of hydroelectric plants, it was noticed that these measures were not able to meet the demands of the affected communities. In the social area, to minimize the impacts, it is common to offer resettlement programs, and for the families that did not accept to be part of these relocation programs, the only alternative was to acquire land inside or outside the micro-regional space, a fact that transformed the population system and the dynamism of commerce and industry, affecting the economic, social and cultural potential of local and regional society.